Ultra-fast real time ethanol sensing behavior and reduction in optical bandgap of the hydrothermally synthesized V2O5/ZnO nanocomposites - Abdul Hakim Shah; Muhammad Anas; Muneerah Alomar; Muhamad Hanif; Muhammad Zubair; Nazir ur Rehman (Chemical Physics Impact)
Owing to the significance of metal oxides based nanostructures for the gas sensing applications, this work reports the hybrid V2O5/ZnO nano-particles/rods nanocomposites (with different V2O5-ZnO contents ratios; (10:1 (VZ-I), 8:1 (VZ-II) and 6:1 (VZ-III)) prepared via hydrothermal method and characterized for structure, morphology, composition, photoluminescence and optical bandgap by XRD, FESEM, EDX, Photo-Luminescence (PL) and UV–Vis spectroscopy, respectively. Structure of the nanocomposite was reported to consist of both V2O5 and ZnO phases, alongwith V2O3 phase in slight amount at the hetero-structure. Morphology of the nanocomposites is observed as V2O5 nanoparticles (∼10–20 nm), densely anchored into the ZnO nanorods (∼500–700 nm), executing a large surface area. PL spectra indicates that the V2O5 emissions peaks get increased in intensity in nanocomposites but decrease with further increase in the ZnO contents. Tauc’s plot is applied to estimate the optical bandgap variation, showing that the bandgap of the nanocomposites lies within those of V2O5 and ZnO individual metal oxides, However, it lowers below that of V2O5 for the VZ-III nanocomposite. Gas sensors based, on the nanocomposites, were tested for sensitivity in static and dynamic response modes at three distinct temperatures, 100, 140 and 190 °C and the VZ-III nanocomposites exhibits a stable and fast response pattern as compared with the other two nanocomposites and hence declares the VZ-III nanocomposites a promising candidate for gas sensors which is explained on the basis of surface redox reactions and energy band models.